2017
DOI: 10.1253/circj.cj-16-1006
|View full text |Cite
|
Sign up to set email alerts
|

Critical Care Management Focused on Optimizing Brain Function After Cardiac Arrest

Abstract: The discussion of neurocritical care management in post-cardiac arrest syndrome (PCAS) has generally focused on target values used for targeted temperature management (TTM). There has been less attention paid to target values for systemic and cerebral parameters to minimize secondary brain damage in PCAS. And the neurologic indications for TTM to produce a favorable neurologic outcome remain to be determined. Critical care management of PCAS patients is fundamental and essential for both cardiologists and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 139 publications
0
5
0
3
Order By: Relevance
“…If rSO 2 is measured in patients with a normal or mildly injured brain, rSO 2 should be correlated with SaO 2 , Hb, and PaCO 2 and not with MAP. This could explain Fick's formula (Nakashima et al, 2017) and display normal CVAR (Sundgreen et al, 2001;Brady et al, 2007;Pham et al, 2015). In this study, only patients in the favorable group at 24 hours were followed with this hypothesis.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…If rSO 2 is measured in patients with a normal or mildly injured brain, rSO 2 should be correlated with SaO 2 , Hb, and PaCO 2 and not with MAP. This could explain Fick's formula (Nakashima et al, 2017) and display normal CVAR (Sundgreen et al, 2001;Brady et al, 2007;Pham et al, 2015). In this study, only patients in the favorable group at 24 hours were followed with this hypothesis.…”
Section: Discussionmentioning
confidence: 83%
“…CBF is described by the Hagen-Poiseuille's equation: CBF = k · ((MAP-ICP) · d 4 )/(L · l) (k: physical constant, MAP: mean arterial pressure, ICP: intracranial pressure, d: cerebral vessel diameter, l: blood viscosity, L: length of vessel). Cerebral vessel diameter is regulated by arterial carbon dioxide pressure (PaCO 2 ) and l is influenced by Hb (Nakashima et al, 2017). In the standard ICU setting for PCAS patients, parameters such as SaO 2 , Hb, MAP, BT, and PaCO 2 are usually evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring of haemodynamic status of patients after CA represents a challenge for the intensivist, as he/she tries to prevent secondary brain damage, which may contribute to further compromise neurological recovery in this setting. 13 No randomised clinical studies are available to help define the optimal haemodynamic strategy to improve neurological outcome after CA, in particular because of the lack of specific goals or targets to individualise treatment. 14 Several studies showed that high lactate levels during the first few hours after ICU admission were predictors of mortality or unfavourable neurological outcome in CA patients.…”
Section: Multivariable Analysismentioning
confidence: 99%
“…Unconsciousness is not only an initial manifestation in post-cardiac arrest syndrome (PCAS), but also a common neurological presentation that persists in intensive care units (ICUs) following resuscitation [ 1 , 2 ]. Brain injury after cardiac arrest is a major factor in determining sustained disability and final mortality of patients with PCAS, which is often terminated by the withdrawal of life-sustaining treatment [ 3 ]. Since the introduction of targeted temperature management (TTM), the timing of the prognosis for patients with comatose PCAS has been conservatively delayed to avoid self-fulfilled prophecy with very early withdrawal of life-sustaining treatment [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%